The Influence of Body Image on Psychological Well-being of Adolescent Girls in Gowa Regency - Nurkhalishah, Fadhilah; Tetteng, Basti; ., Irdianti (Polteknik Ilmu Pemasyarakatan, 2025)
The psychological well-being of teenage girls is starting to be worrying, as evidenced by the low self-acceptance of teenage girls which can give rise to feelings of discomfort with themselves, who will use various means to change their physical appearance. This research aims to determine the influence of body image on the psychological well-being of teenage girls in Gowa Regency. The respondents in this study were 447 teenage girls in Gowa Regency. The sampling technique uses accidental sampling. The significance level of 0.00 (p<0.05), reveals that there is an influence of body image on the psychological well-being of teenage girls in Gowa Regency. The research results show that there is a positive influence, this is proven by a score of R = 0.376 which shows in the direction positive, which means the higher the body image, the higher the psychological well-being, and vice versa. The implications of this research can be used as a basis for teenage girls not to reject the physical changes that occur during the process of growth and development in adolescence.